2011
DOI: 10.1523/jneurosci.0697-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Repetitive Transcranial Magnetic Stimulation of Posterior Superior Temporal Sulcus Improves the Detection of Threatening Postural Changes in Human Bodies

Abstract: Perceiving others' emotions through their body movements and postures is crucial for successful social interaction. While imaging studies indicate that perceiving body emotions relies upon a wide network of subcortico-cortical neural regions, little is known on the causative role of different nodes of this network. We applied event-related repetitive transcranial magnetic stimulation (rTMS) over nonfacial, body-and action-related extrastriate (EBA), temporal (pSTS), and premotor (vPM) cortices to test their ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 83 publications
(101 reference statements)
4
29
0
Order By: Relevance
“…Such model is then warped to a standard mean MRI-based head template (152 subjects – Statistical Parametric Mapping SPM-tool version 2) through affine linear transformation. The present procedure has been successful in previous rTMS studies (Babiloni et al 2006; Harris et al, 2008; Capotosto et al 2009, 2012a, 2012b; Urgesi et al, 2004, 2007; Candidi et al, 2011; Sestieri et al 2013). Of note, while in our pilot studies we observed that rTMS over a ventral region (i.e.…”
Section: Methodssupporting
confidence: 59%
“…Such model is then warped to a standard mean MRI-based head template (152 subjects – Statistical Parametric Mapping SPM-tool version 2) through affine linear transformation. The present procedure has been successful in previous rTMS studies (Babiloni et al 2006; Harris et al, 2008; Capotosto et al 2009, 2012a, 2012b; Urgesi et al, 2004, 2007; Candidi et al, 2011; Sestieri et al 2013). Of note, while in our pilot studies we observed that rTMS over a ventral region (i.e.…”
Section: Methodssupporting
confidence: 59%
“…On the other hand, more recent research using transcranial magnetic stimulation over the right posterior STS revealed a differential role of this region in the perception of threatening compared to neutral stimuli even for static postures (Candidi et al, 2011) and stimulation of this area specifically increased the dominance of fearful body postures over houses in a binocular rivalry paradigm (Candidi et al, 2015).…”
Section: Emotion Motion and Speedmentioning
confidence: 98%
“…There is evidence that activity in body selective regions like the fusiform body area (FBA) [Peelen and Downing, ] and extrastriate body area (EBA) [Downing et al, ] is modulated by emotional information conveyed by bodily expressions [de Gelder et al, ]. In addition to boosting activity in category‐selective brain areas, it has been reported that perceiving body expressions also involves other brain regions; for instance, the amygdala [Hadjikhani and de Gelder, ], cortical and subcortical motor related areas [de Gelder et al, ], superior temporal sulcus [e.g., Candidi et al, ], and periaquaductal gray [van de Riet et al, ].…”
Section: Introductionmentioning
confidence: 99%